2007
DOI: 10.1556/abiol.58.2007.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of lipid peroxide and glutathione redox status of chicken conserning on high dietary selenium intake

Abstract: This study was designed to investigate the effects of excess (24.5 mg Se/kg feed) inorganic and organic dietary selenium supplementation on 3-week-old broilers. The experiments lasted 4 days. Intensity of lipid peroxidation processes (malondialdehyde, MDA) and the amount (reduced glutathione, GSH) and activity (glutathione peroxidase activity, GSHPx) of gluathione redox system were measured in blood plasma, red blood cell hemolysate and liver. Voluntary feed intake in the selenium-treated groups reduced remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Activity of GPx, part of the antioxidant defence system, was not significantly lower in the other hybrids with lower weight gain, which result is partly in agreement with a previous research, which showed a negative correlation between weight gain and GPx activity in pig (Lingaas et al 1991). GPx activity in liver and kidney homogenates showed overall positive correlation with the GSH content, which was also found in our previous experiment with poultry (Balogh et al 2007). This positive correlation can be explained based on the previous data that GPx is an enzyme with allosteric activation property by its substrates (namely hydrogen-peroxide and other oxygen containing free radicals) and co-substrate (GSH) (Perona et al 1978).…”
Section: Discussionsupporting
confidence: 89%
“…Activity of GPx, part of the antioxidant defence system, was not significantly lower in the other hybrids with lower weight gain, which result is partly in agreement with a previous research, which showed a negative correlation between weight gain and GPx activity in pig (Lingaas et al 1991). GPx activity in liver and kidney homogenates showed overall positive correlation with the GSH content, which was also found in our previous experiment with poultry (Balogh et al 2007). This positive correlation can be explained based on the previous data that GPx is an enzyme with allosteric activation property by its substrates (namely hydrogen-peroxide and other oxygen containing free radicals) and co-substrate (GSH) (Perona et al 1978).…”
Section: Discussionsupporting
confidence: 89%
“…Such observation has been made for example in erythrocytes, plasma, kidney and liver of rats fed with a diet containing 3, 6 and 10 mg/kg of Se as selenite or selenomethionine [198]. Other authors observed that excess Se in the diet (both organic and inorganic) was associated with the increased GPx activity in the liver of chicken and, importantly, these changes were accompanied by the toxic effects like increased lipid peroxidation and decreased cell viability [199]. Similar changes linked to the increased GPx activity accompanied by the increased lipid peroxidation have been observed in isolated fish hepatocytes, exposed to toxic dose of selenite [176].…”
Section: Biochemical Evidencementioning
confidence: 85%
“…Reduced glutathione is also involved in the protection from oxidative stress in the infected lungs. GSH is the most important cellular antioxidant and plays a major role in protecting cells against oxidative stress [2]. It has been postulated that loss of GSH may eompromise the cellular antioxidant defense system and lead to accumulation of reactive oxygen species.…”
Section: Biochemical Studiesmentioning
confidence: 99%